Anemia and Body Mass Index Among Children in Malaria Endemic Area - Shinta Liana, Debora; Ratwita Andarsini, Mia; Kurniasih Mappapa, Nurmalinda; Rahmatullah, Ivan; Christina Shanty Larasati, Maria; Dewa Gede Ugrasena, I (Journal of Neonatal Surgery, 2025)
Anemia is a prevalent global health issue frequently encountered by children. Anemia in children may result from iron deficiency or malaria. Anemia, malaria, and the nutritional state of children are believed to be interconnected. This study aimed to examine the correlation between anemia prevalence and the nutritional status of children in malaria-endemic regions, as indicated by TB and/or BMI values. The participants in this study were 394 boys and girls aged over 11 years. The collected data comprised hemoglobin (Hb) levels indicative of anemia, with height, weight, upper arm circumference, and sitting height, which reflect the child's nutritional health. Furthermore, data collecting was conducted about the amount of parental education as a kind of support. The data were evaluated, revealing the correlation between anemia occurrence and children's nutritional state. The findings indicated no significant correlation between the prevalence of anemia with the nutritional status of children, their height, or the educational attainment of parents. One finding indicated a modest significant correlation between the prevalence of anemia and the height of boys. The results indicate that the incidence of anemia does not significantly affect the nutritional status of children